(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Burnout has been the subject of a wide range of research over the years. It reduces work efficiency, increases staff turnover and holds risks for health. This article first gives a theoretical overview of burnout. We focused on police officers and the purpose of this study was to examine the relationship between burnout and sociodemographic data, subjective health status and physical activity. Methodology: In our research, we compiled a questionnaire that includes place of work, working hours, the Maslach Burnout Inventory, a scale for subjective health status, and physical activity. A total of 783 police officers of the Szabolcs- Szatmár-Bereg County Police Headquarters were surveyed. Findings: High emotional exhaustion is found in 4,6% of the workforce surveyed. A high degree of depersonalization occurs in 6%. Considering personal performance, 30% of those surveyed present critical values. Female police officers report statistically higher levels of emotional exhaustion compared to that of male officers. There is a significant correlation between regular physical activity and the levels of depersonalization and personal performance. Value: Our review focuses on the burnout of police officers. It may help to focus attention on the mental health of law enforcement personnel because burnout is one of the most significant contributors to ill health.